2013
DOI: 10.4097/kjae.2013.64.3.229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of meperidine and nefopam for prevention of shivering during spinal anesthesia

Abstract: BackgroundShivering is a frequent event during spinal anesthesia and meperidine is a well-known effective drug for prevention and treatment of shivering. Nefopam is a non-opiate analgesic and also known to have an anti-shivering effect. We compared nefopam with meperidine for efficacy of prevention of shivering during spinal anesthesia.MethodsSixty five patients, American Society of Anesthesiologists physical status I or II, aged 20-65 years, scheduled for elective orthopedic surgery under spinal anesthesia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…Many drugs, including clonidine, dexmedetomidine, tramadol, alfentanyl, and meperidine, have been used to reduce the uncomfortable effects of shivering and prevent shivering related to anesthesia. Although these drugs reduce shivering, they have side effects such as hypotension, bradycardia, sedation, nausea, vomiting, dry mouth, itching, and respiratory depression [3456]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many drugs, including clonidine, dexmedetomidine, tramadol, alfentanyl, and meperidine, have been used to reduce the uncomfortable effects of shivering and prevent shivering related to anesthesia. Although these drugs reduce shivering, they have side effects such as hypotension, bradycardia, sedation, nausea, vomiting, dry mouth, itching, and respiratory depression [3456]. …”
Section: Discussionmentioning
confidence: 99%
“…When nefopam is administered intravenously, a single 20 mg dose should be infused slowly over 15 to 20 minutes to prevent adverse effects such as nausea, cold sweating, dizziness, tachycardia, drowsiness, and injection pain [7]. While the optimum dose of nefopam to prevent shivering has not been determined, Kim et al [6] demonstrated that nefopam at a dose of 0.15 mg/kg provided anti-shivering effects equivalent to that of meperidine. Based on these studies, we chose a dose of 0.15 mg/kg of nefopam administered over 30 minutes to minimize adverse effects and to match the time with the EA group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilotta et al [10] first reported that nefopam was superior to tramadol for the prevention of shivering during neuraxial anesthesia. Also, Piper et al [13] reported that nefopam is better than clonidine for the prevention of postanesthetic shivering whereas Kim et al reported that prophylactic administration of nefopam reduces the incidences and scores of shivering during spinal anesthesia similar to meperidine [14]. Furthermore, nefopam maintained heart rate and mean arterial pressure and this is not surprising as nefopam is known to have positive inotropic and chronotropic effects.…”
Section: Discussionmentioning
confidence: 99%
“…A. Kim et al, 2013). Although Tramadole and Pethidine are available drugs for prevention of POS, however, both drugs could increase intra cranial pressure (ICP) and increase risk of seizure.…”
Section: Introductionmentioning
confidence: 99%